Integrated Quantitative Proteomics and Metabolome Profiling Reveal MSMEG_6171 Overexpression Perturbing Lipid Metabolism of Mycobacterium smegmatis Leading to Increased Vancomycin Resistance - Wu, Zhuhua; Wei, Wenjing; Zhou, Ying; Guo, Huixin; Zhao, Jiao; Liao, Qinghua; Chen, Liang; Zhang, Xiaoli; Zhou, Lin (Frontiers in Microbiology, 2020)
In recent years, the treatment of tuberculosis is once again facing a severe situation because the existing anti-tuberculosis drugs have become weaker and weaker with the emergence of drug-resistant Mycobacterium tuberculosis (Mtb). The studies of cell division and cell cycle-related factors in Mtb are particularly important for the development of new drugs with broad-spectrum effects. Mycobacterium smegmatis (Msm) has been used as a model organism to study the molecular, physiological and drug-resistant mechanisms of Mtb. Bioinformatics analysis has predicted that MSMEG_6171 is a MinD-like protein of the septum site determining protein family associated with cell division in Mycobacterium smegmatis. In our study, we use ultrastructural analysis, proteomics, metabolomics and molecular biology techniques to comprehensively investigate the function of MSMEG_6171. Overexpression of MSMEG_6171 in Msm resulted in elongated cells, suggesting an important role of MSMEG_6171 in regulating cell wall morphology. The MSMEG_6171 overexpression could enhance the bacterial resistance to vancomycin, ethionamide, meropenem and cefamandole. The MSMEG_6171 overexpression could alter the lipid metabolism of Msm to cause the changes on cellular biofilm property and function, which enhances bacterial resistance to antibiotics targetting cell wall synthesis. MSMEG_6171 could also induce the glyceride and phospholipid alteration in vivo to exhibit the pleiotropic phenotypes and various cellular responses. The results showed that amino acid R249 in MSMEG_6171 was a key site that can affect the level of bacterial drug-resistance, suggesting ATPase activity is required for function.